PENGARUH SPIRITUAL QUOTIENT (SQ) TERHADAP PENINGKATAN KINERJA KARYAWAN TRAVEL HAJI DAN UMRAH DI LAMPUNG - Nurhab, Muhamad Irpan (Hirarki : Jurnal Ilmiah Manajemen dan Bisnis, 2024)
The purpose of this research is to see the influence of the Spiritual Quotient (SQ) on increasing the performance of Hajj and Umrah Travel Employees as well as the main factors of Spiritual Quotient (SQ) that have the most influence on increasing the performance of Hajj and Umrah Travel Employees. Umrah travel employees. The number of samples in this research was 100 employee respondents from 10 Hajj and Umrah Travel in Lampung. The research instrument uses a questionnaire, with the analysis methods in this research being Regression Analysis and Factor Analysis. First research results: Spiritual Quotient (SQ) has a significant and positive effect on employee performance, meaning that the better the Spiritual Quotient (SQ) value, the performance of Hajj and Umrah Travel employees will increase and vice versa, the worse it will be. The Spiritual Quotient (SQ) value will be lower. performance of Hajj and Umrah Travel employees. The results of the second study show that patience is the most dominant factor in the Spiritual Quotient (SQ) to improve the performance of Hajj and Umrah travel employees compared to three other factors, namely transcendent awareness, forgiveness, and meaning of life.